Linking photoacclimation responses and microbiome shifts between depth-segregated sibling species of reef corals - Carlos Prada; Tomás López-Londoño; F. Joseph Pollock; Sofia Roitman; Kim B. Ritchie; Don R. Levitan; Nancy Knowlton; Cheryl Woodley; Roberto Iglesias-Prieto; Mónica Medina (Royal Society Open Science, 2022)
Metazoans host complex communities of microorganisms that include dinoflagellates, fungi, bacteria, archaea and viruses. Interactions among members of these complex assemblages allow hosts to adjust their physiology and metabolism to cope with environmental variation and occupy different habitats. Here, using reciprocal transplantation across depths, we studied adaptive divergence in the corals Orbicella annularis and O. franksi, two young species with contrasting vertical distribution in the Caribbean. When transplanted from deep to shallow, O. franksi experienced fast photoacclimation and low mortality, and maintained a consistent bacterial community. By contrast, O. annularis experienced high mortality and limited photoacclimation when transplanted from shallow to deep. The photophysiological collapse of O. annularis in the deep environment was associated with an increased microbiome variability and reduction of some bacterial taxa. Differences in the symbiotic algal community were more pronounced between coral species than between depths. Our study suggests that these sibling species are adapted to distinctive light environments partially driven by the algae photoacclimation capacity and the microbiome robustness, highlighting the importance of niche specialization in symbiotic corals for the maintenance of species diversity. Our findings have implications for the management of these threatened Caribbean corals and the effectiveness of coral reef restoration efforts.